2023
DOI: 10.3390/polym15102375
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinylidene Fluoride/Aromatic Hyperbranched Polyester of Third-Generation-Based Electrospun Nanofiber as a Self-Powered Triboelectric Nanogenerator for Wearable Energy Harvesting and Health Monitoring Applications

Abstract: Flexible pressure sensors have played an increasingly important role in the Internet of Things and human–machine interaction systems. For a sensor device to be commercially viable, it is essential to fabricate a sensor with higher sensitivity and lower power consumption. Polyvinylidene fluoride (PVDF)-based triboelectric nanogenerators (TENGs) prepared by electrospinning are widely used in self-powered electronics owing to their exceptional voltage generation performance and flexible nature. In the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 97 publications
1
11
0
Order By: Relevance
“…The electrospun pristine PVDF show two crystalline peaks at 2θ = 18.3° and 19.8°, which are related to the (110) and (020) α -phase crystalline lattice planes, respectively. Similarly, P-Ar.HBP-G4 main peak is observed at 2θ = 20.6°, which corresponds to the (102) crystalline plane for electroactive β -phase 14 , 48 .
Figure 3 Electrospun P-Ar.HBP-G4 (0–40 wt.-%) blended NFs: ( a ).
…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The electrospun pristine PVDF show two crystalline peaks at 2θ = 18.3° and 19.8°, which are related to the (110) and (020) α -phase crystalline lattice planes, respectively. Similarly, P-Ar.HBP-G4 main peak is observed at 2θ = 20.6°, which corresponds to the (102) crystalline plane for electroactive β -phase 14 , 48 .
Figure 3 Electrospun P-Ar.HBP-G4 (0–40 wt.-%) blended NFs: ( a ).
…”
Section: Resultsmentioning
confidence: 97%
“…FE-SEM analysis revealed that adding Ar.HBP-4 can significantly enhance the output performance of the film when compared to pristine PVDF. This is due to the fact that amount of fluorine element on the surface was decreasing continuously which is replaced by hydrogen and oxygen elements from the addition of Ar.HBP-G4 in PVDF 4 , 48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…17, 18 The high internal impedance and low power density of TENGs are the two main drawbacks that constrain their practical application and higher output efficiencies. 19,20 As a result, across the globe, research communities are striving to establish high-performance TENGs. The choice of materials for TEL used inside the TENG relies on a triboelectric series.…”
Section: Introductionmentioning
confidence: 99%
“…For poly­(vinylidene fluoride) (PVDF)-based TENGs, the vertical CS working mode is suitable choice due to its ease of fabrication. In this method, with tiny air gaps, the TP and TN material layers are vertically stacked in the middle of two electrodes, and the external load causes repeated contact and detachment between the triboelectric layer (TEL) to convert mechanical energy (ME) into electricity. , The high internal impedance and low power density of TENGs are the two main drawbacks that constrain their practical application and higher output efficiencies. , As a result, across the globe, research communities are striving to establish high-performance TENGs. The choice of materials for TEL used inside the TENG relies on a triboelectric series.…”
Section: Introductionmentioning
confidence: 99%